2019
DOI: 10.14740/cr848
|View full text |Cite
|
Sign up to set email alerts
|

Air Entrapment Causing Inappropriate Shock From a Subcutaneous Implantable Cardioverter Defibrillator

Abstract: Subcutaneous implantable cardioverter defibrillator (S-ICD) is an accepted alternative to conventional transvenous devices. Their efficacy in arrhythmia management is comparable to ICDs. However, those devices also have limitations such as lack of anti-tachycardia pacing capability or higher occurrence of device oversensing associated with inappropriate shocks. Air entrapment inside one or more of subcutaneous pockets has been reported as one of uncommon causes of device malfunction. It is important to recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…implanting a replacement device in a subcutaneous pocket that previously housed a larger device may result in pocket air entrapment. Several authors 11,12,18,20–23 . following the instructions of the S‐ICD manufacturer 19 .…”
Section: Discussionmentioning
confidence: 99%
“…implanting a replacement device in a subcutaneous pocket that previously housed a larger device may result in pocket air entrapment. Several authors 11,12,18,20–23 . following the instructions of the S‐ICD manufacturer 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in our patient, there was TWOS due to an increase in T wave amplitude following hyperkalemia, which was corrected after the patient received hemodialysis. Yang et al reported a case of a 58-year-old female patient with a medical history of anthracycline-induced cardiomyopathy with a low ejection fraction who developed TWOS due to artifacts from air entrapment inside the patient [ 14 ]. Our patient did not have any air in her device's pocket.…”
Section: Discussionmentioning
confidence: 99%
“…This malfunction has been reported and requires only reprogramming the device and may be resolved spontaneously. If this complication does not resolve spontaneously, flushing the sternal track with saline, massaging the skin over the lead and suturing over the lead are suggested to minimize air entrapment [16,17,23,25,27,31,38,40,41,46]. Unexpectedly, the IAS were due also to oversensing of chest compressions in the setting of a profound postshock bradycardia.…”
Section: Discussionmentioning
confidence: 99%